Preoperative anemia and postoperative outcomes after hepatectomy. Issue 3 (March 2016) - Tohme, Samer; Varley, Patrick R.; Landsittel, Douglas P.; Chidi, Alexis P.; Tsung, Allan
Abstract: Background: Preoperative anaemia is associated with adverse outcomes after surgery but outcomes after liver surgery specifically are not well established. We aimed to analyze the incidence of and effects of preoperative anemia on morbidity and mortality in patients undergoing liver resection. Methods: All elective hepatectomies performed for the period 2005–2012 recorded in the American College of Surgeons' National Surgical Quality Improvement Program (ACS-NSQIP) database were evaluated. We obtained anonymized data for 30-day mortality and major morbidity (one or more major complication), demographics, and preoperative and perioperative risk factors. We used multivariable logistic regression models to assess the adjusted effect of anemia, which was defined as (hematocrit <39% in men, <36% in women), on postoperative outcomes. Results: We obtained data for 12, 987 patients, of whom 4260 (32.8%) had preoperative anemia. Patients with preoperative anemia experienced higher postoperative major morbidity and mortality rates compared to those without anemia. After adjustment for predefined variables, preoperative anemia was an independent risk factor for postoperative major morbidity (adjusted OR 1.21, 1.09–1.33). After adjustment, there was no significant difference in postoperative mortality for patients with or without preoperative anemia (adjusted OR 0.88, 0.66–1.16). Conclusion: Preoperative anemia is independently associated with an increased risk of major morbidity in patients undergoing hepatectomy. Therefore, it is crucial to readdress preoperative blood management in anemic patients prior to hepatectomy.